?STUDIES ON ANTIBACTERIAL ACTIVITY OF NELUMBIUM SPECIOSUM-WILD SEEDS EXTRACTS (Biological Sciences - PJSIR, 2022)
Seeds of Nelumbium speciosum-Wild were studied for their antibacterial activity against Gram + ve andGrame -vc bacteria in vitro. Ethanolicextract "C" was more active against Gram -ve bacteria than" A" and "B" (aqueousextracts), while extract "A" was more active than "B". Their actions were comparable to the action of Erythrocin,Ampiclox and Pcnbritin.